Sample dimensional reading tests for the fourth year high school - Reyes, Corazon Banag 1933- (1975)
This study presents sample dimensional reading tests for testing comprehension of a reading selection as a whole at the fourth year high school level. Each sample test is designed as a model for structuring a complete set of questions that test the reader's ability to understand the theme or inner meaning of what he reads and arrive at its total concept.
Thesis (M.A.T.)--University of the Philippines
Keywords: Reading (Secondary education).; Reading readiness